2017
DOI: 10.1093/mnras/stx2431
|View full text |Cite
|
Sign up to set email alerts
|

The central spheroids of Milky Way mass-sized galaxies

Abstract: We study the properties of the central spheroids located within 10 kpc of the centre of mass of Milky Way mass-sized galaxies simulated in a cosmological context. The simulated central regions are dominated by stars older than 10 Gyr, mostly formed in situ, with a contribution of ∼ 30 per cent from accreted stars. These stars formed in well-defined starbursts, although accreted stars exhibit sharper and earlier ones. The fraction of accreted stars increases with galactocentric distance, so that at a radius of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 75 publications
1
25
0
Order By: Relevance
“…For example, Cooper et al (2015) and M2019 choose a spherical region of 5 kpc from the galactic center to mark the frontier between stellar halo and bulge. Other authors choose to avoid this spatial segregation, analyzing the overall "central spheroids" (Tissera et al 2018).…”
Section: Bulge Definitionmentioning
confidence: 99%
“…For example, Cooper et al (2015) and M2019 choose a spherical region of 5 kpc from the galactic center to mark the frontier between stellar halo and bulge. Other authors choose to avoid this spatial segregation, analyzing the overall "central spheroids" (Tissera et al 2018).…”
Section: Bulge Definitionmentioning
confidence: 99%
“…We note that the in situ components also contribute with old stars as shown in Tissera et al (2018). Apart from this common feature, each halo has its own peculiarities.…”
mentioning
confidence: 69%
“…They also reported that low-metallicity stars are mainly contributed by low-mass satellites, and are more frequent in the outskirts of halos. The central regions of such systems (within ∼10 kpc, including the bulge), where a significant contribution of old stars was found, have been analyzed in detail by Tissera et al (2018).…”
Section: The Simulated Aquarius Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of low luminosity objects is also relevant in the context of galaxy formation models, where there is a continuous build up of the spheroidal component by accretion of small proto-galactic fragments (e.g., Helmi & White 1999). In this context, Tissera et al (2017) studied the survival of structures in the inner regions of the MW, finding that some remnants may be detected even within the bulge, and the old GCs may be representative (or tracers) of these fragments, and have been useful in studying the formation and evolution of the Galaxy.…”
Section: Introductionmentioning
confidence: 99%